Metabolic preconditioning with minisol: test with infezol 40 - Shejbak, V. M.; Pavljukovec, A. Ju; Doroshenko, E. M. (Sibirskiĭ nauchnyĭ medit︠s︡inskiĭ zhurnal, 2021)
Introduction. We have developed the aminoacid trace element composition «tritarg». The positive effects of tritarg in case of alcohol intoxication were revealed (it prevents the development of amino acid imbalance in the thymus and spleen), a favorable effect is shown when combined with cyclophosphamide (it prevents the decrease in the number of leukocytes in the blood and increases the phagocytic activity of neutrophils). The aim of the work was to analyze the effect of the course introduction of the «tritarg» composition (arginine, taurine, tryptophan and zinc aspartate) on the processes of utilization of amino acids, their primary metabolism in the liver, as well as transformation during passage through the liver. Material and methods. The experiment was conducted on outbred rats weighing 120–140 g. Animals were injected intragastrically for 10 days with tritarg at a dose of 500 mg/kg, 24 hours after the last tritarg administration – once intragastrically infezol 40 at a dose of 20 ml/kg. The animals were decapitated 10 minutes or 45 minutes after infezol 40 administration. Free amino acid content in blood plasma was measured by reverse phase HPLC. Results and discussion. 10 minutes after a single intragastric administration of Infezol40 in the blood plasma of animals that were previously treated with tritarg for 10 days, the total content of amino acids and their nitrogencontaining derivatives increased, the total number of proteinogenic amino acids, essential amino acids, branched-chain amino acids, aromatic amino acids, the ratio arginine/citrulline. The introduction of a mixture of amino acids. 45 minutes after the administration of Infezol 40 in the blood plasma of animals previously treated with tritarg for 10 days, the structure of the pool of amino acids did not differ from the control group. Consequently, the course administration to animals of the amino acid-microelement composition «tritarg» has a multilateral effect on the metabolism as a whole, which becomes apparent with the introduction of a test dose of a full-component aminosol. Conclusion. Thus, we assume that the observed differences in the change in the pool of free amino acids in the experimental groups are due to the fact that course administration of the «tritarg» minisol, including amino acids arginine, tryptophan and taurine, as well as the trace mineral zinc significantly affect the metabolism, proliferative activity and secretion of enzymes.